Sustainable Storytelling by Virtual Influencers: An Experimental Study on the Role of Lifestyle Congruence and Distinctiveness in Shaping Purchase Intentions (Third Sector Social Economic Review, 2026)
This study examines how sustainable storytelling by virtual influencers (VIs) influences consumers’ purchase intentions toward sustainable products. Drawing on narrative and lifestyle congruence perspectives, we propose an integrated model in which storytelling affects purchase intention directly and indirectly through perceived lifestyle congruence and product uniqueness, with VI distinctiveness as a moderator. A between-subjects experimental design was employed using storytelling versus non-narrative manipulations. Data were collected from 150 participants and analysed via SPSS and PROCESS Macro to test the proposed relationships. Results indicate that exposure to sustainable storytelling significantly increases purchase intention compared to non-narrative content. Storytelling also positively influences perceived lifestyle congruence, which in turn enhances perceived product uniqueness. However, product uniqueness does not directly predict purchase intention. Moderated mediation analyses further reveal that the indirect effect of storytelling on purchase intention via lifestyle congruence is significant at medium and high levels of VI distinctiveness, but not at low levels. The findings contribute theoretically by identifying lifestyle congruence as the key mechanism linking sustainable storytelling to purchase intention and by demonstrating that this effect depends on the distinctiveness of virtual influencers. By integrating sustainability, storytelling, and VI research within a moderated mediation framework, the study clarifies the conditions under which narrative persuasion is most effective. In practice, the results suggest that brands, VI designers, and content strategists should emphasise well-crafted sustainable lifestyle narratives and develop distinctive VI personas to strengthen persuasive impact.
Keywords: Virtual influencer; storytelling; narrative transportation; lifestyle congruence; sustainable buying; distinctiveness